(untitled) (Medico Legal Update, 2021)
Introduction: COVID-19 stands for Coronavirus Disease 2019 which is a disease declared as global pandemic on 11th of March, 2020 by the World Health Organization, caused by the newly identified Coronavirus (SARS CoV-2 virus). There is a report of more than 213.6 million confirmed cases of COVID-19 and more than 4.4 million associated deaths globally, according to Johns Hopkins University.(25.08.2021).The present study has the objectives to assess the prevailing knowledge and known information amongst student nurses about the COVID-19 pandemic, the known preventive practices against acquiring and spread of the disease and to learn the preventive practices being used amongst student nurses amidst the pandemic.The setting selected for the study was AIIMS, New Delhi, Nurses Hostel through online mode. A convenient non-probability sampling was adopted for data collection using a structured questionnaire for 2nd year BSc. (Hons) Nursing Students (n=75).The data were obtained and analysis was done in terms of descriptive and inferential statistics. Results showed that 64%, 33.3% ,2.7% nursing students had high, moderate and low level of knowledge (with a score of 18 or more,12-17 and ,lower than 11)respectively. The mean knowledge score was 17.82 for a total score of 24 (74.25%). 57.3%, 40% and 2.7% had high, moderate and low level of performance of preventive practice respectively with a score of 52 or more, 35-51 and lower than 35, and a mean of 51.90 for a total score of 70(74.1%). CONCLUSION: A majority of the study population of nursing students had adequate knowledge who followed adequate preventive practices against the COVID-19 pandemic, however quite a large percentage still had below average knowledge about the disease and an even lower percentage implemented practices for the prevention of acquiring the disease in their daily lives.